Using the Geoelectric Method to Identify Groundwater Schlumberger Configuration Resistivity in the Gambesi and Sasa Villages, South Ternate District, North Maluku Province - Hilda Alkatiri,; Arbi Haya,; Yusdi Akin, (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
One of the geophysical techniques that may be used to define subsurface lithology is the geoelectric approach. The Schlumberger configuration's resistivity technique is used on the assumption that the distance between the potential electrodes is fixed. In contrast, the distance between the current electrodes progressively varies following the resistivity-to-depth curve and the resistivity table. This study aims to determine the lithology of the soil layer and the lithology of the soil layer that serves as an aquifer based on their respective resistivity values. The acquired data demonstrate the presence of multiple layers, including alluvium, sand, gravel, and andesite, in the subsurface lithology at two sites with a depth of 25 meters and a track length of 50 and 100 meters. Based on the resistivity curve to depth and the findings of data processing at the two data collecting sites, groundwater at location 1 (Gambesi Village) could not be identified in the resistivity table because of the location's hilly terrain and alluvial rock types. However, at location 2 (Sasa Village), groundwater was present at depths of 12.8 meters with thicknesses of 6.24 cm and 0.57 Ωm and at depths of 12.8 meters with thicknesses of 4.91 meters and 297 Ωm, respectively. This region slopes down from this position.